2010
DOI: 10.3725/jjn.40.27
|View full text |Cite|
|
Sign up to set email alerts
|

Influence of temperature on pathogenicity of some entomopathogenic nematode isolates (Steinernema spp.) from Japan screened for ability to control some noctuid moth larvae

Abstract: Influence of temperature on pathogenicity of some entomopathogenic nematode isolates (Steinernema spp.) from Japan screened for ability to control some noctuid moth larvae 1,2Mutsuhiro Yoshida 3, Pathogenicity of indigenous steinernematids against some noctuid larvae was examined to screen candidates in a biological control program. First, 17 isolates from ten species (Steinernema feltiae, S. kraussei, S. kushidai, S. litorale, S. monticolum and five RFLP types) were screened for pathogenicity against the midd… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 22 publications
1
2
0
Order By: Relevance
“…The pathogenicity of 17 Japanese isolates of EPNs was tested against the middle instar larvae of P. saucia in a laboratory experiment at different temperatures. Three isolates belonging to S. feltiae caused 70% average mortality at 25°C which is similar to our study (Yoshida, 2010).…”
Section: Resultssupporting
confidence: 80%
See 2 more Smart Citations
“…The pathogenicity of 17 Japanese isolates of EPNs was tested against the middle instar larvae of P. saucia in a laboratory experiment at different temperatures. Three isolates belonging to S. feltiae caused 70% average mortality at 25°C which is similar to our study (Yoshida, 2010).…”
Section: Resultssupporting
confidence: 80%
“…Increase in the time of exposure caused more mortality to last instar P. saucia larvae by all the tested nematode species (Table 1). Similar studies have been carried out to evaluate the effectiveness of EPNs against P. saucia larvae where it was revealed that EPNs have great potential for the management of P. saucia larvae (Yoshida, 2010;Morris and Converse, 2012). The pathogenicity of steirnematid and heterorhabditid nematode species against P. saucia larvae was variable in previous studies.…”
Section: Resultsmentioning
confidence: 91%
See 1 more Smart Citation